Starch-based polymeric materials and nanocomposites : chemistry, processing, and applications - Ahmed, Jasim (Boca Raton : CRC Press, 2012)
'In recent years, much attention has been focused on biodegradable polymers from renewable resources. Due to its availability and low cost, starch is a promising candidate among biopolymers for use in biodegradable packaging materials and for other purposes. Starch-Based Polymeric Materials and Nanocomposites: Chemistry, Processing, and Applications presents the latest developments in starch chemistry, rheology, starch derivatives, starch-based nanocomposites, and their applications.Topics discussed include:The chemistry, microstructure, processing, and enzymatic degradation of starchThe importance and role of starch as a gelling agentPlasticization and the role of plasticizersVarious rheological techniques applied to starch-related products and the characteristics of starch dispersionsPolymeric aspects of reactive extrusion (REX) and its use on starch and other biopolymersCyclodextrins (CDs) and their industrial applications, and CD-based supramole and polymersThe potential of starch in food packaging, edible packaging, feedstock for bioproducts, and industrial and consumer productsThe theoretical basis and derivation of the mathematical model for multicomponent systems and its solution algorithmThe book also explores recent progress in biodegradable starch-based hybrids and nanomaterials and the incorporation of nanoparticles in starches to enhance their mechanical and thermal properties. The book concludes by discussing the use of biopolymeric nanoparticles (BNPs) in drug delivery and life cycle assessment (LCA) of starch-based polymeric materials for packaging and allied applications.With contributions from leading experts in academia and industry, this volume demonstrates the versatility of starch and its potential in a variety of applications'--
'Preface Biodegradable polymers from renewable resources have attracted much attention in recent years. Starch has been considered as one of the most promising candidates among biopolymers mainly because of its attractive combination of availability and price. Starch is unique in its application and versatility. In addition to its contribution to processing industries, research on starch is currently more focused on the development of biodegradable packaging materials and the synthesis of starch derivatives, bionanoparticles, and bionanocomposites. In order to extend applications of starch as primary packaging materials, current research has focused on starch blends, especially starch/polyester (e.g., polylactides [PLA], polycaprolactone [PCL], and polybutylene succinate [PBS]) biodegradable blends. However, starch/polyester are not compatible for blending and, therefore, a reactive compatibilization process known as reactive extrusion is used to synthesize starch/polyester blends at high starch levels (>20 wt%). The process can also be expanded to plasticized starch and nanocomposites by incorporating nanoparticles in the blend. Such nanocomposites exhibit improved stiffness and toughness, solvent and UV resistance, gas barrier properties, thermal stability, and flame retardancy as compared to conventional composites. Rheological and mechanical properties during plasticization and nanocomposite formation provide a better understanding of structural modification and degree of dispersions of nanoparticles into biopolymers'--
Includes bibliographical references and index.
Keywords: Biodegradable plastics; Biopolymers; Nanocomposites (Materials).